Regulation of Nicotiana benthamiana cell death induced by citrus chlorotic dwarf-associated virus-RepA protein by WRKY 1 - Qin, Yangyang; Zhao, Jinfa; Wang, Jiajun; Ye, Xiao; Zhou, Changyong; Zhou, Yan (Frontiers in Plant Science, 2023)
Citrus chlorotic dwarf-associated virus (CCDaV) is a Citlodavirus species in the Geminiviridae family that causes tremendous economic loss to the citrus industry in China. Some proteins encoded by geminiviruses are crucial for the interaction between the virus and its host plant. However, the exact functions of CCDaV-encoded proteins such as CCDaV-RepA have not been investigated. This study presents evidence that CCDaV-RepA elicits a hypersensitive response (HR)-like cell death in Nicotiana benthamiana that was accompanied by the production of H2O2 and ion leakage, which suggested that CCDaV-RepA is a potential recognition target for inducing host defense responses. Furthermore, the rolling-circle replication motifs of CCDaV-RepA are associated with triggering HR-like cell death in N. benthamiana. Confocal microscopy and deletion mutagenesis assays showed that CCDaV-RepA was located in the nucleus, while the first eight amino acids (aa) at the N terminus and two regions located between aa residues 122-263 and 220-264 of RepA were not associated with nuclear localization. Tobacco rattle virus-induced gene silencing of the key signaling cascade components revealed that HR-like cell death induced by RepA was inhibited in WRKY1-silenced N. benthamiana. Moreover, WRKY1 expression was upregulated in RepA-GFP infiltrated Overall, the results suggest that NbWRKY1 positively regulated CCDaV-RepA -induced cell death in N. benthamiana. These findings provide novel information for further research on the interactions between CCDaV and the host plant.